2010
DOI: 10.1002/hyp.7645
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of road‐salt‐contaminated groundwater discharge and estimation of chloride load to a small stream in southern New Hampshire, USA

Abstract: Abstract:Concentrations of chloride in excess of State of New Hampshire water-quality standards (230 mg/l) have been measured in watersheds adjacent to an interstate highway (I-93) in southern New Hampshire. A proposed widening plan for I-93 has raised concerns over further increases in chloride. As part of this effort, road-salt-contaminated groundwater discharge was mapped with terrain electrical conductivity (EC) electromagnetic (EM) methods in the fall of 2006 to identify potential sources of chloride duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…This relationship is comparable with those established in Harte and Trowbridge (2010) and Schalk and Stasulis (2012).…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…This relationship is comparable with those established in Harte and Trowbridge (2010) and Schalk and Stasulis (2012).…”
Section: Methodssupporting
confidence: 88%
“…Groundwater contamination by deicing salt primarily occurs near roads, with severity depending on the amount of salt applied (Foos, 2003; Hon et al, 2009). While runoff quickly removes large amounts of road salt (Ostendorf et al, 2009; Corsi et al, 2010; Harte and Trowbridge, 2010), salt‐contaminated groundwater tends to persist long after road salting ceases due to its relatively low velocity (Williams et al, 2000; Foos, 2003; Bester et al, 2006; Ostendorf et al, 2006; Harte and Trowbridge, 2010; Rhodes and Guswa, 2016).…”
mentioning
confidence: 99%
“…Increases in concentrations of chloride in natural waters from approximately 1945 through 1970 were documented in Hall (1975) where it was noted that increasing concentrations coincided with increased road deicing salt applications. Other studies in New Hampshire have shown that imported road salt may have long-term effects on water quality by raising baseflow concentrations of chloride and sodium due to storage in shallow (Harte and Trowbridge, 2010) and deep (Emery & Garrett Groundwater, Inc., 2007) aquifers. In a regional study of the northern United States, upward trends associated with use of deicing salt for roads and parking areas, number of septic systems, volume of wastewater discharge, and saline groundwater plumes from landfills and salt storage areas were seen in chloride loads (Mullaney and others, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to obtain deicer application amounts applied to these impervious areas were unsuccessful, so an estimate of 30 percent of deicers applied to roads was used to represent deicers applied to parking lots, sidewalks, and driveways. Harte and Trowbridge (2010) estimated that parking lots made up about 50 percent of salt inputs in watersheds adjacent to Interstate 93 in southern New Hampshire. …”
Section: Road Deicing Chemicals and Their Application In The Study Areamentioning
confidence: 99%